Differences in Tooth Size Ratio between Male and Female Patients Reporting to OPD of Orthodontic Department LUMHS, Hyderabad/ Jamshoro (Medical Forum Monthly, 2024)
Objectives: This was a cross sectional study aimed to assess differences in tooth size ratio between male and female patients reporting to OPD of orthodontic department L.U.M.H.SHyderabad/ Jamshoro.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Dental OPD of Orthodontic Department,Liaquat University of Medical & Health Sciences, Hyderabad/ Jamshoro.Materials Methods: The study was carried out on 100 (50 male, 50 female) study casts. Criteria for selection of the study casts were pretreatment orthodontic casts with neutral occlusion (Angle Class I) and fully erupted permanent teeth with no dental anomalies. The individual mesiodistal tooth size was measured with a Boley’s gauge. The mean and standard deviation were calculated for the size of the teeth and the interarch tooth width ratios both anterior and overall.Results: The ratios for the tooth size were compared to the original Bolton ratio. The overall ratio was found to be 91.42 almost equivalent to the original Bolton ratio of 91.3, whereas the anterior ratio was found to be 79.02, higher than the 77.1 as calculated by Bolton. The mean values for the overall and anterior ratio for the male and female subjects determined which were not statistically significant.Standard deviations for overall & anterior ratio were larger than the Boltons’ value.Conclusion: There were no significant differences between the mean overall and anterior tooth width ratio of males and females. Even though the values are not significantly high, a careful analysis of interarch tooth size relationship (Bolton’s ratio) should be added along with other diagnostic considerations before initiating orthodontic treatment for better finishing and stability.